NATIONAL IDENTITY IN THE LIGHT OF ITS DISCURSIVE CONSTRUCTION - Pešić, Milena (National interest, 2023)
The central interest of this paper is the investigation of the phenomenon of national identity from the point of view of its constructional character. With this aim, a synthetic presentation of key modern and postmodern theoretical starting points and ideas that support this line of his conceptualization is given first. Instrumentalist approaches to national identity are observed, which treat it as historically situated and socially and politically constructed, through connection with the phenomena of modernity and the role played by state political projects and state elites in its formation (Hobsbawm, Gellner). Developed on the same basis, national identities were observed through looking at the building of feelings of belonging, solidarity and togetherness, through collective practices of reception and interpretation of common cultural and historical references (Tijes, Renan). As particularly relevant to the topic of this work, we focused on ideas about the imaginary in identity affirmation in settings (Bajar, Anderson), because we consider that line of conceptualization to be the basis of modern understandings of national identity as a primarily mental construct. As an instrument and medium of the nation’s imagination, culture is apostrophized, developed with the emergence of “printed” language. We also find the primacy of culture in Smith’s statements of national identity as constructed on ethnic grounds, based on the concept of cultural configuration. We tried to present contemporary approaches to national identity (Hall, Bhabha, Matrin, Vodak) in the light of their basic common features – the operationalization of modernist concepts in a new constructionist and discursive key. By moving the study into the area of discourse and the process of meaning generation, these approaches deconstruct the metanarratives of the nation, through (linguistic) analysis of their constituents, and seek to explain how national identities are socially constructed through discourse, using language in systematic ways. With this presentation of the development of a complex of ideas and analytical positions, we tried to point out the key assumptions for the creation of modern conceptual-analytical models. At the same time, the scientific basis of the model of discursive construction of national identity created within the framework of the contemporary discourse-historical approach, whose presentation is the second thematic centre of this paper, was demonstrated. This three-dimensional analytical model (macro-theme content, strategies and linguistic means) offered systematic ways of viewing national identity as a product of specific strategies of expression in specific historical and institutional locations, with specific discursive formations and practices. The fact that it is widely used in contemporary case studies best confirms its analytical productivity and indicates the scientific relevance of its theoretical elaborations.